Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic - Baba, Keiji; Wicksten, Mary K. (Zootaxa, 2017)
Eight species of squat lobsters of the genus Uroptychus are reported from the western Atlantic based on the collections of the Museum of Comparative Zoology at Harvard, the Smithsonian Institution and Texas A&M University. Uroptychus nitidus (A. Milne-Edwards, 1880) is reviewed and redescribed, with a syntype taken at Blake Station 200 off Martinique designated as the lectotype. Uroptychus alphonsei n. sp. is named for U. nitidus variety C Chace, 1942, U. fenneri n. sp. for U. nitidus variety A Chace, 1942, and U. janiceae n. sp. for U. nitidus variety B Chace, 1942; U. lindae n. sp. is described on the basis of specimens collected by the Alaminos in the Caribbean Sea off northern Columbia; U. rafai n. sp. is described based on a sole specimen taken from the Straits of Florida; U. reedae n. sp. is described from among the syntypes of U. nitidus; and U. uncifer (A. Milne-Edwards, 1880) is redescribed to elaborate on its specific status, with the designation of lectotype from Blake Station 299 off the coast of Barbados. The number of species of Uroptychus from the western Atlantic now stands at 21. A key to these species is provided.